Activation of the aryl hydrocarbon receptor improves allergen-specific immunotherapy of murine allergic airway inflammation: a novel adjuvant option? - Heine, Sonja; Alessandrini, Francesca; Grosch, Johannes; Graß, Carina; Heldner, Alexander; Schnautz, Benjamin; Grosch, Johanna; Buters, Jeroen; Slusarenko, Benjamin O.; Krappmann, Daniel; Fallarino, Francesca; Ohnmacht, Caspar; et al. (Frontiers in Immunology, 2024)
Background Allergen-specific immunotherapy (AIT) is able to restore immune tolerance to allergens in allergic patients. However, some patients do not or only poorly respond to current treatment protocols. Therefore, there is a need for deeper mechanistic insights and further improvement of treatment strategies. The relevance of the aryl hydrocarbon receptor (AhR), a ligand-dependent transcription factor, has been investigated in several inflammatory diseases, including allergic asthma. However, its potential role in AIT still needs to be addressed. Methods A murine model of AIT in ovalbumin-induced allergic airway inflammation was performed in AhR-deficient (AhR-/-) and wild-type mice. Furthermore, AIT was combined with the application of the high-affinity AhR agonist 10-chloro-7H-benzimidazo[2,1-a]benzo[de]iso-quinolin-7-one (10-Cl-BBQ) as an adjuvant to investigate the effects of AhR activation on therapeutic outcome. Results Although AhR-/- mice suffer stronger allergic responses than wild-type mice, experimental AIT is comparably effective in both. Nevertheless, combining AIT with the administration of 10-Cl-BBQ improved therapeutic effects by an AhR-dependent mechanism, resulting in decreased cell counts in the bronchoalveolar fluid, decreased pulmonary Th2 and Th17 cell levels, and lower sIgE levels. Conclusion This study demonstrates that the success of AIT is not dependent on the AhR. However, targeting the AhR during AIT can help to dampen inflammation and improve tolerogenic vaccination. Therefore, AhR ligands might represent promising candidates as immunomodulators to enhance the efficacy of AIT.